Pluralisme Agama di Indonesia dan Tantangannya Serta Pandangan Gereja Katolik Tentang Pluralitas Agama - Sesfao, Marianus; Nabu, Gaudensius (JURNAL PROPHETA, 2021)
Indonesia has a motto Bhineka Tunggal Ika. It means unity in diversity. Thismotto binds all of Indonesian people to not to discriminate one nation from another,including race, skin color, religion, language, etc. The proper attitude in plurality is torespect and to appreciate one another. To respect and to appreciate are social basicattitudes that relevant in every encounter and togetherness with the others. Without these attitudes, our lives will be so vapid and full of social tensions because each personjust to prioritize his/her own interests and neglect even spoil the others’ interests.Respect and appreciation are shown by the act of recognition that there are the otherswho need to be noticed beside ourselves. Fraternity is a gift. This gift is a graceful lifethat makes us become Jesus’ brothers and sisters in the family of God. It is because faithand love, not because of blood relationship, feeling and the descendant. BhinekaTunggal Ika: a lot gifts but one Spirit.